2016
DOI: 10.1038/nature20600
|View full text |Cite
|
Sign up to set email alerts
|

Resolved images of a protostellar outflow driven by an extended disk wind

Abstract: Young stars are associated with prominent outflows of molecular gas. The ejection of gas is believed to remove angular momentum from the protostellar system, permitting young stars to grow by the accretion of material from the protostellar disk. The underlying mechanism for outflow ejection is not yet understood, but is believed to be closely linked to the protostellar disk. Various models have been proposed to explain the outflows, differing mainly in the region where acceleration of material takes place: clo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
160
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(175 citation statements)
references
References 34 publications
14
160
0
1
Order By: Relevance
“…Recent low-velocity and poorly-collimated CO outflow was found to come from the disk surface at larger disk radii of up to 25 AU from the central source 6 . All these suggest the presence of a disk wind component extracting the angular momentum from the disk at larger radii.…”
Section: ′′mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent low-velocity and poorly-collimated CO outflow was found to come from the disk surface at larger disk radii of up to 25 AU from the central source 6 . All these suggest the presence of a disk wind component extracting the angular momentum from the disk at larger radii.…”
Section: ′′mentioning
confidence: 99%
“…Molecular outflows have been found to trace low-velocity ( ∼ < 20 km s −1 ) extended winds coming out of the disks down to ∼ 10 AU scales [2][3][4][5][6] . They are found to be rotating and thus can remove angular momentum from the disks in the outer part, allowing the disk material in the wind-launching region to accrete.…”
mentioning
confidence: 99%
“…Fielding et al (2015) considered this possibility and found that the change in disk orientation over time was larger than that set by the stellar spin. Recent ALMA studies have investigated the opening angle and velocity distribution on ∼ 10 au scales: Class 0 source HH46/47 has both jet-like and wide-angle components , while the outflow of Class I source TMC1a is best described as a wide-angle disk-wind (Bjerkeli et al 2016). Thus, the launching mechanism may also vary among sources and over time.…”
Section: Star-formation Efficiencymentioning
confidence: 99%
“…Louvet et al 2016) because of the limited spectral resolution and wavelength accuracy in the optical. Sub/mm interferometric observations do not have this limitation and have provided clear evidence for flow rotation in several younger protostellar sources, although at lower speeds than the axial jets, suggesting ejection from ∼5−25 au in the disk (Launhardt et al 2009;Matthews et al 2010;Bjerkeli et al 2016; Hirota et al 2017). Thermo-chemical models show that dusty DWs launched from this range of radii would indeed remain molecular despite magnetic acceleration (Panoglou et al 2012).…”
Section: Introductionmentioning
confidence: 99%